Keltner's psychiatric nursing - Steele, Debbie (Elsevier, 2023)
Gain the skills you need to provide safe and effective psychiatric nursing care! Keltner's Psychiatric Nursing, 9th Edition provides a solid foundation in the knowledge required to manage and care for patients with psychiatric disorders. It features a unique, three-pronged approach to psychotherapeutic management emphasizing the nurse's three primary tools: themselves and their relationship with patients, medications, and the therapeutic environment. New to this edition are Next Generation NCLEX® exam-style case studies to help you learn clinical judgment and prepare for success on the NCLEX. Known for its clear and friendly writing style, this text covers psychiatric nursing like no other book on the market.